The chemistry of Brazilian Leguminosae. LX. Indolylacetic acid from Tachigalia paniculata - Dias, Silvia M. C.; Maia, José Guilherme Soares; Ferreira, Zenaide S.; Gottlieb, Otto R. (Acta Amazonica, 1982)
The ethanolic extract of trunk wood of Tachigalia paniculata Ducke (Leguminosae-Caesalpinioideae) was found to contain substantial quantities of 2-(3-indolyl)-acetic acid.